Coagulation status in coronary artery disease patients with type II diabetes mellitus compared with non-diabetic coronary artery disease patients using the PFA-100® and ROTEM® - Feuring, Martin; Wehling, Martin; Burkhardt, Heinrich; Schultz, Armin (Platelets, 2010)
Previous investigations in patients with coronary artery disease (CAD) revealed differences in thromboelastographic parameters indicating different states of coagulability. The aim of the present study was to investigate the coagulation status of patients with documented CAD and type II diabetes mellitus (DM) and non-diabetic patients with coronary artery disease with the PFA-100® and the ROTEM®. No differences were found in platelet function as measured with collagen/epinephrine (263.6 ± 70.6 s vs. 254.6 ± 65.3 s) and collagen/ADP cartridges (105.3 ± 63.2 s vs. 90.6 ± 47.3 s) in CAD patients with DM and CAD patients without DM. Measured with the EXTEM reagent of the ROTEM®, mean maximum clot elasticity (MCE) in patients with CAD and DM (233.6 ± 86.9) was significantly longer than in CAD patients without DM (186.7 ± 54.5), (p = 0.03). A similar result was seen using the INTEM reagent; patients with CAD and DM (234.4 ± 83.9) showed a higher value for MCE than CAD patients without DM (190.8 ± 57.8) which was of borderline significance (p = 0.053). Moreover, a weak trend for higher maximum clot firmness (MCF) was seen in CAD patients with DM compared with CAD patients without DM with the EXTEM reagent (68.1 ± 7.5 vs. 63.6 ± 8.6, p = 0.08) and the INTEM reagent (68.4 ± 7.2 vs. 64.1 ± 8.2, p = 0.09). The ROTEM® analysis indicates increased coagulability in patients with coronary artery disease and diabetes mellitus compared to non-diabetic CAD patients. Moreover, the ROTEM® device seems to be an appropriate and easy-to-use tool to describe the coagulation status in these patients groups.